Morphometry of indian roofed turtle, Pangshura tecta (Gray 1831) in Bangladesh - Hossain, Md Lokman; Sarker, Shorab Uddin; Sarker, Noor Jahan (Bangladesh Journal of Zoology, 2015)
Morphometric study was conducted on Indian roofed turtle, Pangshura tecta, between January 1997 and December 2000 in several district of Bangladesh. The mean weight of adult male was 92.6 ± 13.3 g and of female 441.1 ± 185.4 g. The length and width of carapace as well as those of the plastron and the height of the shell varied with the body weight of the turtle. The percentage of hard parts of the body weight of P. tecta was 35.8 ± 2.5 %, whereas percentage of soft parts of the body weight was 64.2 ± 2.5 %. The average weight of the female P. tecta was 4.8 times higher than that of the male. Bangladesh J. Zool. 41(2): 207-215, 2013